KEBIJAKAN FORMULASI HUKUM PIDANA DALAM PENANGGULANGAN MALPRAKTEK KEPERAWATAN - Dg. Patompo, Mohammad Fadli (Katalogis, 2018)
The problem formulation in this research were: (1) How is nursing malpracticeeperceived in review to criminal law policy?and (2) How is nursing malpracticeperceived in review to criminal law formulation in the future? The objectives of the Research were to identify nursing malpractice in review to criminal law formulation policy and to identify and analyze Nursing malpractice in review to criminal law formulation in the future. It was a juridical normative research. Thesources of the legal materials were primary material, secondary material and nonlegal supporting material. It adopted legal approaches, concept and cases. The legal data were collected by inventorying legal data and documents through bibliographic alstudies The analysis was descriptive and conclusion was taken based on the problem discussed. Based on th estudy result, it was concluded that thep revailing positive laws, either set forthin the Indonesian Criminal Codes, Law number 36 year 2009 about health, Law number 44 about Hospital, Law number 8 Year 1999 about customer protection or Law number 38 about year 2014 about nursing practice, do not provide about nursing administrative breach, But not abou tcrimina lsanction in case of nursing malpractice. In the future policy formulation, It is advisable to formulate nursing law and corporate accountabilities in case of nursing malpractice causing losses and injuries to patiens due to nursing mal praktice.